2015
DOI: 10.1080/10810730.2014.965368
|View full text |Cite
|
Sign up to set email alerts
|

The Health Literacy and ESL Study: A Community-Based Intervention for Spanish-Speaking Adults

Abstract: Although Hispanics have a documented high risk of limited health literacy, there is a scarcity of research with this population group, and particularly with Hispanic immigrants who generally confront language barriers that have been related to low health literacy. The National Action Plan to Improve Health Literacy identified community-based English-language instruction as a strategy that can facilitate a health literate society. However, the literature lacks discussion on this type of intervention. This rando… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
61
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 30 publications
(25 reference statements)
2
61
0
Order By: Relevance
“…Similarly, numerical skills were taken into account only in the studies by Soto‐Mas et al. (,b), and their omission may be deemed a limitation of the other studies reviewed. This same problem was highlighted by the US Agency for Healthcare Research and Quality, which found that the strength of evidence for the relationship between numeracy and health outcomes was insufficient or low, given the small number of studies (Berkman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, numerical skills were taken into account only in the studies by Soto‐Mas et al. (,b), and their omission may be deemed a limitation of the other studies reviewed. This same problem was highlighted by the US Agency for Healthcare Research and Quality, which found that the strength of evidence for the relationship between numeracy and health outcomes was insufficient or low, given the small number of studies (Berkman et al.…”
Section: Discussionmentioning
confidence: 99%
“…Four curricula reported results from evaluations designed to assess their effectiveness in improving students' health literacy Elder et al, 1998Elder et al, , 2000Soto Mas et al, 2014;Soto Mas, Ji, Fuentes, & Tinajero, 2015;Taylor et al, 2009Taylor et al, , 2011. All reported evaluations were conducted by the curriculum developers=personnel.…”
Section: What Are the Goals And Health Topics Of These Curricula?mentioning
confidence: 99%
“…The first one (Soto Mas et al, 2014) consisted of a pretest-posttest design assessing students' health literacy with the Spanish version of the Test of Functional Health Literacy in Adults (Parker, Baker, Williams, & Nurss, 1995). The second one (Soto Mas et al, 2015) comprised a randomized control trial, and the results showed a significantly higher increase in scores on the Test of Functional Health Literacy in Adults for the intervention group compared to the control group. This latest curriculum was evaluated using a health literacy measurement tool, whereas other curricula measured a specific dimension of health literacy, such as knowledge and communication skills.…”
Section: What Are the Goals And Health Topics Of These Curricula?mentioning
confidence: 99%
“…Moreover, all used an experimental study design. The study participants were recruited from the following settings: community partnerships [10], through local radio and television stations [9], community nurse [7], via English-asa-second-language classrooms [8], and social and welfare clubs [11]. All but two studies [8,9], which both added health information to language courses, used different types of interventions such as: 1) workshops wherein health information was presented to the participants, with the use of activities such as lectures, role-play exercises, demonstrations, drama, group presentations and group discussions [10], 2) a community conference wherein awareness was raised, mainly among the local health care providers, about the Somali Bantu refugees' presence in the American community, their culture and their information needs, with additional education for Somali Bantu refugee mothers about necessary health information through welcome packages [7], and 3) an online depression information intervention, consisting of multilingual information about depression [11].…”
Section: Characteristics Interventions Retrieved Through Pub Medmentioning
confidence: 99%
“…Only one study [9] specifically conducted measurements to gain outcomes about health literacy, and used the Test of Functional Health Literacy in Adults (TOFHLA) for this. Another study [11] aimed to measure depression literacy directly, which is a specific type of (mental) health literacy, through the Analyses of Variances (ANOVA).…”
Section: Outcomes Interventions Retrieved Through Pub Medmentioning
confidence: 99%